2015
DOI: 10.1155/2015/543928
|View full text |Cite
|
Sign up to set email alerts
|

Oral Allergy Syndrome: An Update for Stomatologists

Abstract: Oral allergy syndrome (OAS) is an allergic reaction in the oral cavity subsequent to the consumption of food such as fruits, nuts, and vegetables. It occurs mainly due to homology of proteins of pollen to the proteins of fruits and vegetables. In OAS, the immune system produces antibodies that are directed against the proteins of pollen and structurally similar proteins in food, hence, resulting in allergic symptoms limited mainly to the oral cavity. In this review, we have summarized the etiopathogenesis, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…s1, s3, s6, and s9 respectively represent serum samples from subjects 1, 3, 6, and 9 in the soybean group. as patients are thought to be sensitized initially to pollen allergens [31]. We confirmed that recombinant Gly m 3 and 4 are reactive with serum IgE from a soybean allergy patient, and showed that these two allergens are present in the soybean extract using a specific antibody produced in our laboratory (data not shown).…”
Section: The β-Subunit Of Soybean 7s Globulin As a Percutaneously Sensupporting
confidence: 70%
See 1 more Smart Citation
“…s1, s3, s6, and s9 respectively represent serum samples from subjects 1, 3, 6, and 9 in the soybean group. as patients are thought to be sensitized initially to pollen allergens [31]. We confirmed that recombinant Gly m 3 and 4 are reactive with serum IgE from a soybean allergy patient, and showed that these two allergens are present in the soybean extract using a specific antibody produced in our laboratory (data not shown).…”
Section: The β-Subunit Of Soybean 7s Globulin As a Percutaneously Sensupporting
confidence: 70%
“…In addition, 4.2% of patients in their study were allergic to soybean upon food challenge, and those patients developed severe symptoms and needed to be administered anti-allergy medication. Soybean allergies develop not only in infants at a high incidence rate (class 1 food allergy), but also in adult patients with pollinosis (class 2 food allergy) [30,31]. Therefore, it remains an important task to gain a better understanding of soybean allergies.…”
mentioning
confidence: 99%
“…Gly m 5, Gly m 6, and TI are known as class 1 food allergens but Gly m 3 and Gly m 4 are known as class 2 food allergens. It is popularly believed that whereas class 1 food allergens are resistant to heat and digestion, class 2 food allergens do not have these properties (10). In addition, the content of Gly m 3 and Gly m 4 are less than Gly m 5, Gly m 6, and TI.…”
Section: Discussionmentioning
confidence: 99%
“…Act d 8 (15–18 kDa) is one of pathogenesis‐related (PR‐10) proteins that is found to be homologous to birch pollen (Agarwal & Agarwal, ; Oberhuber et al., ). They are unstable proteins which can be eliminated through thermal processing (for example, cooking or steaming; Kashyap & Kashyap, ). Act d 11 has been recognized as one of the main ripening‐related proteins present in kiwifruit (D'Avino et al., ).…”
Section: Main Kiwifruit Allergensmentioning
confidence: 99%